Building lactams by highly selective hydrodeoxygenation of cyclic imides using an alumina-supported AgRe bimetallic nanocatalyst - Carles Lluna-Galán; Juan Camilo Arango-Daza; Daviel Gómez; Patricia Concepción; Rong Sun; Jose J. Calvino; Laura Simonelli; Rosa Adam; Jose R. Cabrero-Antonino (Nature Communications)
Abstract The rational design of robust nanocatalysts containing the suitable active sites for building relevant organic compounds, such as lactams, is a desired approximation towards the development of a sustainable fine chemistry field. In that sense, the design of a proper nanomaterial able to mediate the selective hydrodeoxygenation of cyclic imides to lactams with high tolerance to the preservation of aromatic rings remains rather unexplored. Here, we show the design of a bimetallic AgRe nanomaterial with notable activity and selectivity to mediate this transformation affording more than 60 lactams from the corresponding imides. Interestingly, in this work we disclose that the optimal AgRe nanocatalyst is constituted by AgReO4 nanoaggregates that undergo an in situ hydrogenative dispersion to form the active centers composed by Ag0 nanoparticles and ReOx species. Deep characterization, together with kinetic and mechanistic studies, have revealed that the intimate Ag-Re contact intrinsic to AgReO4 species is key for the formation of the most active catalytic sites and the proper bimetallic cooperation required for mediating the desired process.